Kenyan Government Initiatives in Slum Upgrading - (:unkn) unknown (My University, 2011)
This article discusses two Kenyan government initiatives in slum upgrading: the Kenya Slum Upgrading Programme (KENSUP) and the Kenya Informal Settlement Improvement Project (KISIP). It gives the objectives, strategies and components of each programme. The article focuses on the KENSUP programme, presenting the achievements of this slum upgrading initiative to date and sums up with the challenges facing slum upgrading in Kenya.
Keywords: African Research